Molecular phylogeny of Oreochromis (Cichlidae: Oreochromini) reveals mito-nuclear discordance and multiple colonisation of adverse aquatic environments - Ford, Antonia G.P.; Bullen, Thomas R.; Pang, Longson; Genner, Martin J.; Bills, Roger; Flouri, Tomáš; Ngatunga, Benjamin P.; Rüber, Lukas; Schliewen, Ulrich K.; Seehausen, Ole; Shechonge, Asilatu; Stiassny, Melanie L.J.; et al. (Molecular phylogenetics and evolution, 2019)
[Display omitted] •A comprehensive phylogeny of the continental African cichlid genus Oreochromis is presented.•Considerable mito-nuclear discordance is identified.•Multiple adaptation to adverse (elevated thermal and saline) conditions.•Likely support for a single transition to extreme (soda-lake) conditions.•A taxonomic revision of the genus Alcolapia is proposed. Although the majority of cichlid diversity occurs in the African Great Lakes, these fish have also diversified across the African continent. Such continental radiations, occurring in both rivers and lakes have received far less attention than lacustrine radiations despite some members, such as the oreochromine cichlids (commonly referred to as ‘tilapia’), having significant scientific and socio-economic importance both within and beyond their native range. Unique among cichlids, several species of the genus Oreochromis exhibit adaptation to soda conditions (including tolerance to elevated temperatures and salinity), which are of interest from evolutionary biology research and aquaculture perspectives. Questions remain regarding the factors facilitating the diversification of this group, which to date have not been addressed within a phylogenetic framework. Here we present the first comprehensive (32/37 described species) multi-marker molecular phylogeny of Oreochromis and closely related Alcolapia, based on mitochondrial (1583 bp) and nuclear (3092 bp) sequence data. We show widespread discordance between nuclear DNA and mitochondrial DNA trees. This could be the result of incomplete lineage sorting and/or introgression in mitochondrial loci, although we did not find a strong signal for the latter. Based on our nuclear phylogeny we demonstrate that adaptation to adverse conditions (elevated salinity, temperature, or alkalinity) has occurred multiple times within Oreochromis, but that adaptation to extreme (soda) conditions (high salinity, temperature, and alkalinity) has likely arisen once in the lineage leading to O. amphimelas and Alcolapia. We also show Alcolapia is nested within Oreochromis, which is in agreement with previous studies, and here revise the taxonomy to synonymise the genus in Oreochromis, retaining the designation as subgenus Oreochromis (Alcolapia).